Feeding behavior of lambs fed diets containing peach palm meal - Santos, Alana Batista dos; Pereira, Mara Lúcia Albuquerque; Silva, Herymá Giovane de Oliveira; Pereira, Taiala Cristina de Jesus; Ribeiro, Leandro Sampaio Oliveira; Azevêdo, José Augusto Gomes; Sousa, Leandro Borges; Sousa, Larisse Borges; Silva, Samille Neres da; Ferreira, Fabiano Andrade; Barreto, Fernando Oliveira (Semina: Ciências Agrárias, 2016)
The aim of this study was to evaluate the feeding behavior of lambs fed diets containing peach palm meal replacing maize (0, 10, 40, 60, and 85% DM). Thirty Santa Inês sheep with an average initial body weight of 21.6 Â± 0.87 kg were distributed in a completely randomized design with five diets and six replicates. Feeding time in min kg-1 DM and min kg-1 NDFap increased by 34 min and 99.6 min, respectively, with each level of substitution of maize for the peach palm meal. Rumination and chewing times, in min kg-1 DM and min kg-1 NDF, also increased in response to the substitution of maize for peach palm meal. When expressed in min day-1, rumination and chewing activities decreased by 12.4 and 14.6 min, respectively, as the amount of peach palm meal in the concentrate was increased. The time spent idle increased linearly (P < 0.05), by 14.6 min day-1, with the replacement levels, compared with the control diet. Peach palm meal in the composition of sheep diets reduces the intakes of dry matter and fiber and decreases the feed and rumination efficiencies. Replacing maize by peach palm meal increases the feeding time and rumination and chewing activities of feedlot lambs.